National identity in Singapore - Mohammed Shah Reza (2008)
This paper examines the use of rhetorical devices in the government’s discourse to craft national identity. Using Fisher’s narrative paradigm as the underlying framework for analysis, this study focuses on Prime Minister Goh Chok Tong’s discourse in the National Day Rally speeches during the period of 1997 to 2003.